Perlindungan Hak Waris Anak Perkawinan Campuran atas Aset Bisnis Lintas Batas Berdasarkan Asas Lex Rei Sitae - Indah Riyanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Cross-border marriages increasingly produce estates composed of land, buildings, company shares, receivables, intellectual property, and digital business assets located in different jurisdictions. This study examines how children born from mixed marriages can obtain effective inheritance protection when the estate is affected by the lex rei sitae principle and by restrictions attached to the location or legal form of the asset. The research uses a normative legal method with statutory, conceptual, comparative, and case approaches, supported by a matrix of Indonesian legal instruments and recent scholarship on private international law and business succession. The analysis shows that a child’s status as an heir should be separated from the capacity to hold, register, or control a particular asset. Lex rei sitae provides strong certainty for immovable property, but its blanket application to all business assets creates fragmentation because shares, receivables, intellectual property, and digital assets require different connecting factors. The study proposes a calibrated protection model that coordinates lex successionis, lex rei sitae, lex societatis, mandatory rules, and the best interests of the child. This model requires early asset mapping, valid proof of parentage and citizenship, succession planning, liquidity safeguards, and coordinated recognition procedures across jurisdictions.